Hematological toxicities associated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 2 (6th November 2019) - Wong, Evelyn Y. T.; Tan, Grace H. C.; Kumar, Mrinal; Teo, Melissa C. C.
Abstract: Introduction: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) have been found to prolong survival in selected patients with peritoneal disease, but the extent of cytoreduction and chemoperfusion can result in systemic toxicities. We evaluate the incidence of perioperative hematological complications and its associated risk factors. Methods: Retrospective analysis of a prospectively collected database of CRS‐HIPEC cases between April 2001 and October 2016 was performed. Patients were stratified based on the clinicopathological characteristics, perioperative incidence, grade, and duration of leukopenia (white blood cells < 4000/mm 3 ), neutropenia (absolute neutrophils < 2000/mm 3 ), and thrombocytopenia (platelets < 140 000/mm 3 ). Results: Two hundred and thirty‐five CRS‐HIPEC were performed in 220 patients with peritoneal metastasis of colorectal, ovarian, primary peritoneal, appendiceal, or mesothelioma origins. The incidences of leukopenia, neutropenia, and thrombocytopenia were 15.3%, 3.8%, and 37.9%, respectively. Median time to onset was 1 day (0‐16 days), 0 day (0‐2 days), and 1 day (1‐2 days), respectively, after operation. Median duration of leukopenia, neutropenia, and thrombocytopenia was 1 day (1‐3 days), 1 day (1‐2days), and 3 days (range 0‐16 days), respectively. Age > 60 (odds ratio [OR] 0.229 [95% CI: 0.105‐0.502], P < .001) and the use of prior chemotherapy (OR 2.46 [95% CI: 1.24, 4.83], P = .010) were independent risk factors for thrombocytopenia on multivariable logistic regression. Conclusion: Hematological toxicities are common after hyperthermic intraperitoneal chemotherapy with thrombocytopenia being most common. Patients with age > 60, and who have undergone chemotherapy, are at risk of these toxicities and should be closely monitored post CRS‐HIPEC.